2012
DOI: 10.1155/2012/781236
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Nanostructured Ti‐W Oxides Films for Efficient Electrochromic Windows

Abstract: With the aim to enhance the electrochromic (EC) efficiency and electrochemical stability of electrochromic devices (ECD), mixed nanostructured TiO2/WO3films were prepared by an electrochemical deposition method with the purpose of adding WO3nanoparticles to porous nanocrystalline doctor-blade TiO2(nc-TiO2) films. The results of the characterization of electrochromic properties in 1 M LiClO4+ propylene carbonate (LiClO4+ PC) of both the nc-TiO2/F-doped tin oxide (FTO) and WO3/TiO2/FTO configurations showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…In particular, the work by Yoshimura et al [26] pointed at the importance of conducting the sputtering at unusually high pressures (that are known to promote nanocrystallinity [107], analogously to the case of gas evaporation [108]). Furthermore, our observed coloration efficiencies are consistent with those in some studies on films prepared by sol-gel deposition [38], chemical bath deposition [41,43], and doctor blade technique [54,55]. Our earlier work on sputter deposition in the presence of CF 4 in order to make titanium oxyfluoride films is yet the one that produced the highest coloration efficiency (cf.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, the work by Yoshimura et al [26] pointed at the importance of conducting the sputtering at unusually high pressures (that are known to promote nanocrystallinity [107], analogously to the case of gas evaporation [108]). Furthermore, our observed coloration efficiencies are consistent with those in some studies on films prepared by sol-gel deposition [38], chemical bath deposition [41,43], and doctor blade technique [54,55]. Our earlier work on sputter deposition in the presence of CF 4 in order to make titanium oxyfluoride films is yet the one that produced the highest coloration efficiency (cf.…”
Section: Resultssupporting
confidence: 90%
“…Thus a doctor blade technique has been employed recently by Dinh et al [54,55] and has given TiO 2 films with η ≈ 34 cm 2 /C.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other, supporting studies on the electrochromism in W-Ti oxide have been reported for films prepared by sputtering [16][17][18][19], chemical technology involving spraying [20][21][22] dipping [16,23] or spinning [24][25][26], electrodeposition [27,28] and anodization [29]. The enhanced stability has been investigated in depth in recent work on W-Ti oxide films made by sputtering [30,31] and chemical techniques [26].…”
Section: Introductionmentioning
confidence: 91%
“…Since these drawbacks have proven difficult to overcome in a pure WO 3 system there have been a number of attempts to solve them by doping or mixing with other electrochromic materials, usually another transition metal oxide. [9][10][11][12][13][14][15][16] In 2005, Patil et al…”
mentioning
confidence: 99%
“…Since these drawbacks have proven difficult to overcome in a pure WO 3 system there have been a number of attempts to solve them by doping or mixing with other electrochromic materials, usually another transition metal oxide. [9][10][11][12][13][14][15][16] In 2005, Patil et al 17 investigated the effect of TiO 2 additions on the electrochromic properties of tungsten trioxide films prepared through spray pyrolysis, finding improved electrochromic reversibility, but not any real enhancement of the coloration efficiency. 17 One possible way to improve electrochromic efficiency is to tailor the morphology of the oxide to have spacious channels that can aid charge/ion injection into and transport within the film.…”
mentioning
confidence: 99%